The Effect of Consumer Characteristics and Lifestyle toward Purchase Decision - Rahmah, Khairunnisa; Satyaninggrat, Luh Made Wisnu (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2023)
Coffee is a significant commodity in terms of both consumption and production. As a result, marketing interactions with systems and activities must be capable of bringing consumers closer to the items and corporate brand names offered. Urban neighborhoods are currently undergoing lifestyle adjustments. The consumption patterns exhibited by certain cohorts of persons who frequent coffee establishments might be viewed as a reflection of contemporary societal norms and values. The aim of this research is to determine the characteristics of customers and to examine the impact of the consumer lifestyle connected with XYZ Coffee on consumer buying decisions. The research employed a non-probability sampling method, especially convenience sampling, consisting of a sample size of 271 participants. The data were analyzed using descriptive statistics and Structural Equation Modeling (SEM). The study's findings indicate that the target demographic for XYZ Coffee products consists of economically active individuals with adequate income and substantial expenditures on food and beverages. This consumer segment is characterized by a favorable lifestyle and image, making them the primary purchasers of XYZ Coffee products.